Legal aspects on brazilian land use and sil and water conservation - Cunha, Pedro; Alípaz, Suzana; Santos, Devanir Garcia dos (Sociedade & Natureza, 2005)
The National Water Agency - ANA is responsible for the implementation of the National Water Resources Policy, that policy mentioned in the Law n. º 9.433/97, has to be integrated to the others, municipalities, estate and federal Policies, on the soil and water conservation aspects, to obey the item VI, of article 24, from the Federal Constitution, amongst others laws listed below: Law n.º 9.984/00 Law n.º 6.225/75 Therefore, a specific law does not exist but a delegation of powers to the Ministry of Agriculture for the promotion, supervision and orientation of the national land use and soil conservation policy. This competence was executed through programs of that Ministry and despite the generated advances, for example, with the National Program of Watersheds, that had success in some states of the south and southeastern region, in years 70 and 80, but it had problems. The implementation of these programs was subjects to the interests of the governing and ministers who had occupied the folder of the Ministry of Agriculture, occurring discontinuities and not having of fact the creation and implantation of one policy of state on national land use and soil and water conservation. It is in the context of the interaction of the soil and water conservation with the water availability and its multiple uses, imposes the implantation of one national land use and soil and water conservation policy, better formatted, in order to prevent discontinuities. However, even so all the related legal body to the subject mentions "incentives" for the soil and water conservation, its viability is tied necessarily with the regulation of these devices, that never was considered and remains in open. Had the great interaction between soil and water and considering the effect that the land use and the conservation of the soil on the quality and quantity of water from the watershed, consider it is proposed the articulation and development of one national land use and soil and water conservation policy.